Pembuatan Motion Graphic Iklan Aplikasi FlickApp dan Silvi+ di PT Kreigan Sentral Teknologi - Rahmani, Diana Putri; Ardelia Wirastuti, Merry; Fakhiratunisa, Nabila; Farras Fauzan, Mochamad; Ronald Suhada, Vandame; Fitria Devi Fitriani, Mira; Alif Falah, Naufal; Lintar Balle, Joddy; Rizha, Teuku; Siskandar, Ridwan (Jurnal Sains Indonesia, 2021)
The rapid technology development has a major impact on the economic activities that develop in the community. The number of products and services that have sprung up today makes entrepreneurs have to compete to get the attention of consumers so that they are not less competitive. PT. Kreigan Sentral Teknologi, which is engaged in digital finance, currently has 2 mobile applications, namely FlickApp and Silvi +, but the company does not have advertisements regarding related applications so that these applications are not widely known by the public. Therefore the company needs an interesting and informative promotional media. The purpose of this project is to produce a promotional media which including the information about FlickApp and Silvi+ in the form of motion graphics using Adobe XD, Adobe Illustrator, and Adobe After Effect.